RELATIONSHIP BETWEEN MACROECONOMIC FUNDAMENTALS, BANK’S CREDIT SCHEME, FIRM’S PERFORMANCE AND FIRM’S VALUE DIMENSIONS - Harmono Harmono (Jurnal Keuangan dan Perbankan, 2017)
This study investigated the relationship among macroeconomic fundamentals, bank’s credit scheme, firm’s performance, and firm’s value dimensions.  The research design was explanatory research, using a structural equation model. The sample is PT. Bank Persero industry in Indonesia from 1999-2014 monthly. Empirically, based on confirmatory test it could be described that the variables represented for each dimension were that the dominant variable in macroeconomic was currency exchange rate IDR to USD, and working capital interest rate represented the bank credit interest scheme dimension, ROA was dominant for firm’s performance, and the frequency of stock trading was representing the firm’s value dimension. For the next, based on a structural equation model with a regression coefficient, path analysis could be discussed as follows. First, the working capital credit interest rate was as weak mediation variable between exchange rate IDR to USD and ROA. Second, working capital credit interest rate influenced the frequency of stock trading through ROA. In this case, ROA was a strong mediation variable. The last path analyzed the influence of exchange rate IDR against USD to the frequency of stock trading through ROA. Here ROA was the strong mediation variable.